2014
DOI: 10.1063/1.4899075
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of hydrogen storage in binary hydrogen-methane clathrate hydrates

Abstract: Articles you may be interested inTheoretical prediction of hydrogen storage on Li-decorated boron nitride atomic chains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…We conjecture that if enough H 2 is supplied, more 5 12 cages would be filled, and increased pressure would make more H 2 enter the hydrate phase even when the pressure is above 80 MPa. Consequently, with a high percentage of H 2 in the gas phase, one can store more H 2 in the mixed hydrate, which has been predicted by theoretical evolution with the van der Waals and Platteeuw statistical thermodynamic model from Belosludov et al…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…We conjecture that if enough H 2 is supplied, more 5 12 cages would be filled, and increased pressure would make more H 2 enter the hydrate phase even when the pressure is above 80 MPa. Consequently, with a high percentage of H 2 in the gas phase, one can store more H 2 in the mixed hydrate, which has been predicted by theoretical evolution with the van der Waals and Platteeuw statistical thermodynamic model from Belosludov et al…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, both CH 4 and H 2 are fuel gases, and H 2 + CH 4 binary hydrates should have high energy density. However, there are few studies on H 2 + CH 4 binary hydrates, and most of them are on thermodynamic properties. As the binary hydrates grown at high thermodynamic driving force do not resemble the composition of the most stable crystal, we conjecture that growth kinetics of hydrates can affect the overall energy storage, the details of which are difficult for experimental studies to probe because of the temporal and spatial limitation. It should be noted that the only molecular dynamics study on binary hydrate growth containing H 2 was performed by Song et al They reported the growth of binary hydrates with the mW water model and two highly soluble guest molecules (H 2 and THF), where the guest model parameters were chosen to resemble the size of H 2 and THF.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical potential of guest molecules in the gas phase were calculated using the following equations for a non-ideal gas mixture with a Lennard–Jones interaction between molecules [20]:μig(V,T)=kBTln[NigV(2π2miT)3/2]Nig(NkBTln(1Ni,jεijxigxjgV)N2i,jσijxigxjgV), where εi and σi are Lennard–Jones parameters. Interaction parameters between molecules of different types are defined by the combination rules εij=εiεj and …”
Section: Methodsmentioning
confidence: 99%
“…The direct use of a CO 2 + N 2 gas mixture (20 mol% CO 2 and 80 mol% N 2 to reproduce flue gas from a power plant) instead of pure CO 2 greatly enhances the overall CH 4 recovery rate in complex marine systems and reduces the costs [11] of CO 2 separation from flue gas. A great number of experimental and theoretical studies concerning the stability and composition of gas hydrates formed from gas mixtures has been published in the last decade [6,12,13,14,15,16,17,18,19,20,21,22]. In particular, a comparison of numerous experimental data on phase equilibria in a water–methane–carbon dioxide and a water–nitrogen–carbon dioxide systems were presented in papers [23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The direct use of a (CO2 + N2) gas mixture (20 mole% CO2 and 80 mole% N2 to reproduce flue gas from a power plant) instead of pure CO2 greatly enhances the overall CH4 recovery rate in complex marine systems and reduces costs [11] of CO2 separation from flue gas. Great number of experimental and theoretical studies concerning stability and composition of gas hydrates formed from gas mixtures has been published in last decade [6,[12][13][14][15][16][17][18][19][20][21][22]. In particular, comparison of numerous experimental data on phase equilibria in systems watermixture of methane and carbon dioxide, water-mixture of nitrogen and carbon dioxide were presented in papers [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%